Uma sequência de ensino-aprendizagem : movimento circular como proposta para o ensino remoto - Vieira, Késia Cristina dos Santos (2021)
The present work has as main goal to present a Teaching-Learning Sequence (TLS) planned to work the Circular Motion content, especially the study of centripetal acceleration, as a proposal for remote learning, which can also be adapted to presential perspective. The theme was subsidized according to David Ausubel’s theory of meaningful learning, to support with elaboration of a material that was potentially significative and in identification of previous knowledges presents in the student’s cognitive structure. To guide in definitions of learning objectives, presents in TLS’s structure, was counted with Revised Taxonomy of educational objectives. This TLS integrate the IpC methodology with use of technological tools (ICT), in order to enhance learning interactively. The classes were organized to worked synchronously and asynchronously. For this, TLS was divided in three moments. The first moment count with a didactic agreement and project presentation, application of a diagnostic test, video and a game about vectors. The second moment consists in providing a e-book, an online class about circular movement using PHET Simulation and an adaptation of Peer Instruction (PI) method. In the last moment, the application of a post-test and an evaluation survey about educational product. Against first moment, was verified that previous knowledges were based on common sense. The availability of a potentially significant material, in second moment, was presented as primordial requirement for the PI method implantation. In post-test, was evidenced that TLS proposal led the students to a constructive learning, this being based on levels of remember, understand and apply. Therefore, we conclude that the teaching-learning sequence on circular motion proved to be satisfactory in the construction of learning in the perspective of remote learning.